Ciclo Biológico de (bactericera cockerelli) bajo condiciones controladas, en tres localidades Salache, Cotopaxi 2020. - Falconez Portilla, Johana Elizabeth (2020)
The present investigation was carried out in three locations, under controlled conditions, in Salache, Machachi and Saquisili, where the behavior and habits of the insect (Bactericera cockerelli.), Responsible for the transmission of the phytoplasma known as purple point in potato cultivation, were determined. (Solanum tuberosum). The breeding and collection of B. cockerelli was carried out within the main nightshade producing areas such as the provinces of Cotopaxi and Pichincha, in which each stage of development of the insect was evidenced and where high rates of damage have been reported. by the same, in potato crops consisted in the observation and development of the insect, feeding, was carried out with the use of fresh foliage and potato plants, which were placed in tubs to later place them in glass cages;, placing them in a fresh and shaded, in Salache, they were kept in a breeding room (entomology laboratory) at an average temperature of 21 ºC and relative humidity of 68% with a total cycle of 31 days, under these conditions they were maintained throughout the development, in Saquisili were maintained with an average relative humidity of 75%, and a temperature of 13.9 ° C with a total cycle of 33 days and in Machachi a temperature of around 17 ° C and a relative humidity of 74% with a total cycle was maintained. 34 days. The data recorded throughout the process were: number of eggs deposited, development time of each nymphal stage and duration of the adult stage. The observations were made during the months of October, November and December, where the data of the first instants of B. cockerelli were recorded until its last stage, managing to determine that the Saquisili locality had a rapid oval development of 2 to 6 days and the oldest locality in the adult stage of B. cockerelli was Salache, which also obtained the best development in the total biological cycle of the species.